Multi-Agent Coordination under Uncertain Communication - Bhargava, Nikhil (Proceedings of the AAAI Conference on Artificial Intelligence, 2019)
Multi-agent coordination is not a simple problem. While significant research has gone into computing plans efficiently and managing competing preferences, the execution of multiagent plans can still fail even when the plan space is small and agent goals are universally aligned. The reason for this difficulty is that in order to guarantee successful execution of a plan, effective multi-agent coordination requires communication to ensure that all actors have accurate beliefs about the state of the world. My thesis will focus on the problem of characterizing, modeling, and providing efficient algorithms for addressing planning and execution when there agents cannot maintain perfect communication.